EFFECTS OF SUSTAINABLE AWARENESS TOWARDS SUSTAINABLE PRODUCT PURCHASE DECISION (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
Purchasing and using goods for daily necessities produce large amounts of waste. “Reduce, Reuse, Recycle” has become a well-known consumer waste management philosophy. Consumers are increasingly crucial in environmental protection efforts, and sustainable consumption is the epitome of environmental protection behavior. Sustainable awareness plays an important role in sustainable product purchase decisions. This research aims to determine the effects of sustainable awareness, such as reduce, reuse, and recycle, on sustainable product purchase decisions. This research uses quantitative methods to process the data associated with a phenomenon. The unit of analysis used is the individual, with a total of 487 valid responses. The Indonesian citizen population includes Baby Boomers, Gen X, Y, and Z. Primary data was obtained by filling out questionnaires. The sampling technique used was purposive sampling. Data analysis techniques in this study use multiple linear regression, the classic assumption test, the T-test and F-test, and the coefficient of determination using the SPSS software program. The results of  this research states that there is significant positive effects of sustainable awareness, including reduce, reuse, and recycle, on sustainable product purchase decisions.
Keywords: Reduce; Reuse; Sustainable Awareness; Sustainable Product Purchase Decision